Economic and Democratic Consolidation of the Former Yugoslav Republics - Hacek, Miro (Political Preferences, 2022)
Article analyses the processes of democratic consolidation in the former Yugoslav republics in the period since the volatile and violent breakup of socialist Yugoslavia three decades ago. Author is putting an emphasis on the notion of economic consolidation processes in all former Yugoslav republics and tests the thesis that economic consolidation is indeed the one prerequisite of democratic consolidation that suffered most direct effects of failed peaceful transformation in areas of former Yugoslavia that plunged into post-independence wars and conflicts. Author confirms that the secret to the democratic resilience is hidden in economic development – not only, as some theories claimed back in the 1960s (Lipset, 1959, p. 69–105), in various forms of undemocratic rule, but in a democracy built upon democratic institutions, respect for human rights and fundamental freedoms plus the rule of law.